Multi-System Inflammatory Syndrome in Children (MIS-C) with Retropharyngeal Involvement Mimicking Abscess: the Therapeutic Role of Anakinra - Troisi, Angela; Accomando, Francesco; Mambelli, Lorenzo; Marchetti, Federico (Archives of Clinical and Medical Case Reports, 2023)
Multi-System Inflammatory Syndrome in Children (MIS-C) is a new diagnostic entity that appeared with the Covid-19 pandemic, and that only concerns the pediatric age. Early diagnosis and early immunomodulatory treatment lead most of the time to a complete resolution of the pathology. We present a case of MIS-C, whose main clinical feature was neck pain due to inflammation of retropharyngeal tissues. The use of anakinra was critical for healing.